From tax deduction to tax rebate: A philosophical reconstruction of zakat–tax integration in Indonesia - Adillah, Erika Rishan; Mukhlas, Oyo Sunaryo; Burhanuddin, Burhanuddin (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
This study examines the normative and philosophical foundations of zakat–tax integration in Indonesia by critically assessing the limitations of the existing tax deduction mechanism and proposing a transition toward a rebate-based model. Although zakat payments made through authorized institutions are formally recognized as deductible expenses, this policy has failed to provide substantive fiscal relief and has produced a persistent double burden for Muslim taxpayers. Employing a normative legal research method with an interdisciplinary orientation integrating legal philosophy, legal pluralism, maqāṣid al-sharīʿah, and comparative analysis this study analyzes Indonesia’s zakat–tax framework and contrasts it with Malaysia’s rebate system. The findings show that Indonesia’s deduction model marginalizes zakat as a fiscal institution, contradicts principles of distributive justice, weakens legal legitimacy, and limits zakat’s redistributive function. In contrast, Malaysia’s rebate model eliminates the double burden by allowing zakat to directly reduce tax payable, thereby enhancing compliance, fiscal justice, and institutional coherence. This study argues that the core problem of zakat–tax integration in Indonesia is paradigmatic rather than administrative. Accordingly, it proposes a rebate-based integration model supported by regulatory reform, institutional collaboration, and digital governance. The study contributes theoretically by reconstructing zakat–tax relations through a legal-philosophical lens and practically by offering a policy-oriented framework for a more just and pluralistic fiscal system in Indonesia.